Fritz W. Bistrup et al. (red.): Mindeblade om Danmarks-ekspeditionen 1906-08. (Det Grønlandske Selskabs Skrifter XXV. Publikationer om Østgrønland nr. 10, Kbh., 1983). 124 s. - Kjær Sørensen, Axel (Historie/Jyske Samlinger, 1985)
-